Tribological properties of brass materials and their application for cages in rolling bearings. (March 2014) - Laumann, S.; Jisa, R.; Deinhofer, G.; Franek, F.
<x content-type="archive" xml:space="preserve">Abstract</x> The continuously growing demands on standard components of machine elements with respect to power density, efficiency and durability while operating can reach the borders of load bearing capacity and lead to premature failure. Especially in engineering applications with insufficiently predictable operating conditions, bearings can usually meet these requirements. Possible correctives are the use of new materials with modified properties or changes in the design. In the railway industry, particularly high impact loads on bearing cages can occur. Brass cages are primarily used here. Thus, new brass alloys are applied whose properties have been improved in terms of their mechanical and tribological behaviour. Various brass alloys have been selected on the basis of the mechanical properties and cost aspects. Using a modified test rig for precision bearings, these alloys have been studied with respect to the tribological properties, which are correlated with the results of tests with brass rolling bearing cages. This gives the possibility to choose optimised brass materials for bearing cage application under increased requirements.